Improving Social Interaction Competence in Incarcerated Adolescents Through Group Therapy: A Quasi-Experimental Study - Manurung, Idawati; Amperaningsih, Yuliati (Chakra Brahmanda Lentera Institute, 2026)
Background: Social interaction competence is essential for the successful rehabilitation of juvenile offenders. However, empirical evidence on structured group therapy targeting social interaction competence among incarcerated adolescents in low-resource correctional settings remains limited. This study aimed to evaluate the efficacy of a module-based group therapy intervention in improving social competence and to identify the environmental factors influencing these outcomes. Methods: A quasi-experimental pretest-posttest with control group study was conducted with 80 adolescents (primarily aged 16–17). The intervention group (n=44) received a structured group therapy program, while the control group (n=36) received standard institutional care. Data were analyzed using paired t-tests, independent samples t-tests, and multivariate regression to identify predictors of social competence. Data were collected using a questionnaire and a validated social interaction scale (Cronbach’s alpha = 0.905). Results: The intervention group demonstrated a statistically significant improvement in social interaction scores, increasing from 54.64±15.43 to 63.45±12.65 (p < 0.05), with a medium-to-large effect size (Cohen’s d = 0.62). Conversely, the control group showed no significant change (p > 0,05, d = 0.42). Multivariate analysis revealed that while age was a positive predictor of competence (beta = -0.20, p < 0.05), the length of detention emerged as a notable negative factor (beta = -0.36, p < 0.05), suggesting a